2015
DOI: 10.5719/hgeo.2015.91.3
|View full text |Cite
|
Sign up to set email alerts
|

A GIS-based Multicriteria Decision Making Approach for Evaluating Accessibility to Public Parks in Calgary, Alberta

Abstract: This paper presents a Geographic Information System based Multicriteria Decision Making approach for evaluating accessibility to public parks in Calgary, Alberta. The approach involves the weighted linear combination with the for obtaining entropy weighting method the criterion (attribute) weights. The paper demonstrates a core-periphery pattern of accessibility to public parks in Calgary. Furthermore, the pattern has shown tendency to be more polarized between the year of 2006 and 2011. The results of this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“…In this method, first, three zones are generated around the centroid of each population block based on the service area of mini, neighborhood and community parks (see Table 1), and then the number of parks that are within these service areas is determined. Finally, the ratio of the number of parks to the block population can be calculated according to Equation 1 (Meng et al, 2015).…”
Section: Covering Methodmentioning
confidence: 99%
See 2 more Smart Citations
“…In this method, first, three zones are generated around the centroid of each population block based on the service area of mini, neighborhood and community parks (see Table 1), and then the number of parks that are within these service areas is determined. Finally, the ratio of the number of parks to the block population can be calculated according to Equation 1 (Meng et al, 2015).…”
Section: Covering Methodmentioning
confidence: 99%
“…Data pre-processing consists of a four stages procedure: The first stage involves the classification of the parks into three groups according to their area, including mini parks with an area of less than one acre, neighborhood parks with an area between one to twenty acres and community parks with an area between 20 up to 50 acres (Mertes et al, 1995). The reason for the classification is that different types of public parks, such as mini, neighborhood, and community parks, have different sizes of service areas (Meng et al, 2015). Table 1 shows the classification of parks and the assignment of their respective service area.…”
Section: Data and Data Pre-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…In that research, the authors identified that a significant number of existing bridges are not placed at the optimal locations, through a comprehensive consideration of the map of flood area and the connection of existing bridges in that area. In 2015, Meng et al [5] introduced GIS-MCDM method to assess the access to public parks in Calgary, Alberta, and conducted a research on the optimal site condition considering regional traits with different accessibility conditions.…”
Section: Previous Researches On Mcdm and Gis-based Decision Making Prmentioning
confidence: 99%
“…Decision making is a framework in which useful information regarding with selecting an alternative from a set of alternatives is driven from row data layers. In spatial decision making, alternatives are points, lines and polygons which have a number of attribute values (Meng & Malczewski, 2015).…”
Section: Multi Criteria Decision Makingmentioning
confidence: 99%